Adolescents' approach-avoidance behaviour in the context of pain. Issue 2 (February 2016) - Fisher, Emma; Keogh, Edmund; Eccleston, Christopher
Abstract : Abstract: Adolescents who experience pain often face competing goals and have to choose whether to approach (confront) or avoid pain. This study investigates the decisions adolescents make when their pain conflicts with a valued goal. Adolescents between the ages of 15 and 18 years (N = 170) completed questionnaires on general and pain-specific anxiety, courage, and dispositional avoidance. Adolescents were presented with 16 vignettes (8 high pain intensity, 8 low pain intensity), which described pain conflicting with a goal (eg, doing well at school, seeing friends). Adolescents rated goals for importance and reported how likely they would be to approach or avoid each pain. Adolescents were more likely to avoid and were more fearful of high pain intensity than low pain intensity vignettes. Pain anxiety predicted higher levels of avoidance for both pain intensities. General anxiety was not a significant predictor of avoidance for either pain intensity. Goal importance promoted approach of goals, but only when pain was described as intense. However, pain anxiety predicted avoidance beyond the importance of goals for high pain intensity vignettes. In addition, we compared approach-avoidance of adolescents with and without chronic pain; analyses revealed no differences in approach-avoidance behaviour. We also found that behavioural endurance was predictive of approach and dispositional avoidance predicted higher avoidance, but courage was not predictive of behaviour in this task. We adopt a motivational perspective when interpreting the findings and consider whether the fear-avoidance model should be extended to include the function of avoidance or approach in the pursuit of a desired goal. Abstract : Pain-specific anxiety predicted the avoidance of painful activities beyond the importance of goals in adolescents. General anxiety did not predict approach-avoidance behaviours.Supplemental Digital Content is Available in the Text.